2010
DOI: 10.1128/mcb.01428-09
|View full text |Cite
|
Sign up to set email alerts
|

Osteocyte Wnt/β-Catenin Signaling Is Required for Normal Bone Homeostasis

Abstract: ␤-Catenin-dependent canonical Wnt signaling plays an important role in bone metabolism by controlling differentiation of bone-forming osteoblasts and bone-resorbing osteoclasts. To investigate its function in osteocytes, the cell type constituting the majority of bone cells, we generated osteocyte-specific ␤-catenindeficient mice (Ctnnb1 loxP/loxP ; Dmp1-Cre). Homozygous mutants were born at normal Mendelian frequency with no obvious morphological abnormalities or detectable differences in size or body weight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
385
3
17

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 527 publications
(444 citation statements)
references
References 72 publications
(125 reference statements)
39
385
3
17
Order By: Relevance
“…(31) These data extend previous reports demonstrating that osteocyte-specific deletion of b-catenin is associated with an increase in the RANKL/OPG ratio, thereby supporting a role of this signaling pathway in balancing the expression of these opposing factors. (34) In vitro experiments using primary and established osteocyte cells have demonstrated that the Wnt inhibitor, sclerostin, stimulates RANKL expression, leading to an increase in the RANKL/OPG mRNA ratio favoring the formation of TRAP þ multinucleated cells. (68) These studies are also in agreement with our data demonstrating that the increased sclerostin expression observed early in CKD-MBD leads to a concomitant increase in RANKL expression that may drive osteoclastogenesis, which was associated with increased bone formation rates in the jck mouse.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(31) These data extend previous reports demonstrating that osteocyte-specific deletion of b-catenin is associated with an increase in the RANKL/OPG ratio, thereby supporting a role of this signaling pathway in balancing the expression of these opposing factors. (34) In vitro experiments using primary and established osteocyte cells have demonstrated that the Wnt inhibitor, sclerostin, stimulates RANKL expression, leading to an increase in the RANKL/OPG mRNA ratio favoring the formation of TRAP þ multinucleated cells. (68) These studies are also in agreement with our data demonstrating that the increased sclerostin expression observed early in CKD-MBD leads to a concomitant increase in RANKL expression that may drive osteoclastogenesis, which was associated with increased bone formation rates in the jck mouse.…”
Section: Discussionmentioning
confidence: 99%
“…(32)(33)(34) Furthermore, serum levels of the Wnt/b-catenin antagonists, sclerostin (SOST) and Dickkopft-1 (DKK1), were recently reported to be elevated in individuals on dialysis compared to non-CKD individuals, raising the possibility that repression of the b-catenin signaling pathway may also occur in the setting of CKD. (69) The importance of b-catenin signaling on bone mass and remodeling has been well studied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations